2021
DOI: 10.1074/jbc.ra120.015452
|View full text |Cite
|
Sign up to set email alerts
|

Comparative interactomes of HSF1 in stress and disease reveal a role for CTCF in HSF1-mediated gene regulation

Abstract: Heat Shock Transcription Factor 1 (HSF1) orchestrates cellular stress protection by activating or repressing gene transcription in response to protein misfolding, oncogenic cell proliferation and other environmental stresses. HSF1 is tightly regulated via intramolecular repressive interactions, post-translational modifications, and protein-protein interactions. How these HSF1 regulatory protein interactions are altered in response to acute and chronic stress is largely unknown. To elucidate the profile of HSF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 111 publications
0
19
0
Order By: Relevance
“…This is in line with a previous report that showed an involvement HSF1 in the induction of RNA-producing enhancers across the whole genome, but also the recruitment of HSF1 in CTCF-rich, non-transcribed chromatin [ 32 ], suggesting that interactions between HSF1 and CTCF are possible. Indeed, such interactions were later documented [ 33 ]. We also showed that HSF1 is likely to interact with CTCF in MCF7 cells (as assessed by the proximity ligation assay) and the number of interactions increased significantly after heat shock treatment ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with a previous report that showed an involvement HSF1 in the induction of RNA-producing enhancers across the whole genome, but also the recruitment of HSF1 in CTCF-rich, non-transcribed chromatin [ 32 ], suggesting that interactions between HSF1 and CTCF are possible. Indeed, such interactions were later documented [ 33 ]. We also showed that HSF1 is likely to interact with CTCF in MCF7 cells (as assessed by the proximity ligation assay) and the number of interactions increased significantly after heat shock treatment ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…It was previously suggested that HSF1 may be involved in remodeling 3D chromatin architecture in response to temperature stress [ 49 ] and recruited into CTCF-occupied, non-transcribed chromatin [ 32 ]. We showed here the interaction of HSF1 with CTCF, a known regulator of chromatin architecture that was proposed to act in repressing specific HSF1 target genes [ 33 ]. This indicates that HSF1 may regulate transcription directly (by binding to the promoters) and indirectly by participating in chromatin organization.…”
Section: Discussionmentioning
confidence: 99%
“…We note that RPRD1B function in the HS response is unlikely to be due to a direct interaction with HSF1. Indeed, several proteomic studies have established the HSF1 interactome, and RPRD1B was not identified as a partner in these experiments ( Burchfiel et al, 2021 ; Smith et al, 2022 ; Takii et al, 2019 ; Zhang et al, 2019 ). Furthermore, HSF1 appears to be normally activated in cells depleted for RPRD1B.…”
Section: Resultsmentioning
confidence: 99%
“…Several HSPs are downregulated in cells and mouse models of HD, which is known to contribute to mtHTT aggregation [138,153,154]. HSF1 depletion has also been reported in several cell and mouse models of HD, in human iPSCs derived from patienetse with HD differentiated into MSN-like cells, and in human postmortem striatum from pateinets with HD [138,[155][156][157][158]. Initial studies proposed that down-regulation of HSPs in HD was facilitated by mtHTT-mediated changes in chromatin remodeling [153].…”
Section: Ck2α' Facilitates Protein Homeostasis In Hdmentioning
confidence: 99%